2019
DOI: 10.1111/aas.13502
|View full text |Cite
|
Sign up to set email alerts
|

Association of global DNA hypomethylation with post‐operative cognitive dysfunction in elderly patients undergoing hip surgery

Abstract: Post-operative cognitive dysfunction (POCD) is a decline in cognitive status after surgery, typically manifesting as alterations in orientation, memory, thinking, attention, insight or other aspects of central nervous system function. 1 POCD can last for a few days to years and is associated with adverse effects, including increased surgical morbidity and mortality, hospitalization and out-of-hospital care costs. For patients older than 60 years-of-age, POCD occurred in 25% to 40% of patients 1 week after non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…To name one landmark study included in the meta-analysis, the International Study of Post-Operative Cognitive Dysfunction (ISPOCD 1), found that among 1011 older surgical patients recruited in eight European countries and the USA, patients with more than a high school education had even a halved risk of POCD at one week after surgery compared with patients with less than high school education ( Moller et al 1998 ). Studies from various European and Asian countries and the USA that were not included in the 2017 meta-analysis ( Grichnik et al 1999 ) or published thereafter ( Bendikaite and Vimantaite 2020 ; Ehsani et al 2020 ; Huang et al 2020a ; Klinger et al 2019 ; Li et al 2020 ; Wang et al 2018 ; Yuhe et al 2020 ; Zhang et al 2019 ; Zhou et al 2020 ) too, consistently indicate that patients with a lower educational level are at increased POCD risk at discharge ( Zhang et al 2019 ) within days of surgery ( Ehsani et al 2020 ; Li et al 2020 ; Zhao et al 2020 ; Zhou et al 2020 ) but also during six to 12 weeks after surgery ( Grichnik et al 1999 ; Yuhe et al 2020 ). The fact that observations extend to several months after surgery is important because studies on POCD with longer follow-up periods offer preferred scope for conclusions: during shorter follow-up periods immediate effects of surgery on brain function including a potential influence of POD can prevail.…”
Section: Cognitive Epidemiology In a Surgical Settingmentioning
confidence: 99%
“…To name one landmark study included in the meta-analysis, the International Study of Post-Operative Cognitive Dysfunction (ISPOCD 1), found that among 1011 older surgical patients recruited in eight European countries and the USA, patients with more than a high school education had even a halved risk of POCD at one week after surgery compared with patients with less than high school education ( Moller et al 1998 ). Studies from various European and Asian countries and the USA that were not included in the 2017 meta-analysis ( Grichnik et al 1999 ) or published thereafter ( Bendikaite and Vimantaite 2020 ; Ehsani et al 2020 ; Huang et al 2020a ; Klinger et al 2019 ; Li et al 2020 ; Wang et al 2018 ; Yuhe et al 2020 ; Zhang et al 2019 ; Zhou et al 2020 ) too, consistently indicate that patients with a lower educational level are at increased POCD risk at discharge ( Zhang et al 2019 ) within days of surgery ( Ehsani et al 2020 ; Li et al 2020 ; Zhao et al 2020 ; Zhou et al 2020 ) but also during six to 12 weeks after surgery ( Grichnik et al 1999 ; Yuhe et al 2020 ). The fact that observations extend to several months after surgery is important because studies on POCD with longer follow-up periods offer preferred scope for conclusions: during shorter follow-up periods immediate effects of surgery on brain function including a potential influence of POD can prevail.…”
Section: Cognitive Epidemiology In a Surgical Settingmentioning
confidence: 99%
“…Only a few studies thus far have evaluated post-operative acute epigenetic changes for any kind of surgery (except bariatric surgery). [13][14][15] Studies have shown alterations in gene-speci c and global DNA methylation levels during and after the surgery; however, no consistent trend has been reported. [13][14][15] Again, no study has explored long-term and persistent epigenetic changes after the surgery (except in the case of bariatric surgery).…”
Section: Discussionmentioning
confidence: 99%
“…However, similar results were observed in the processes of aging and carcinogenesis. 9 , 38 Indeed, studies on PND have also observed global DNA hypomethylation, 11 , 39 and DNA hypermethylation of several genes (e.g. glucocorticoid receptor, Arc, Bdnf, Reln, PSD‐95 ), 10 , 40 , 41 indicating that the global DNA methylation status did not necessarily reflect the methylation of specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…transcription factors) 8 . An imbalance of DNA methylation has been regarded as a valuable biomarker for aging and aging‐related pathologies, including PND 9–11 . Importantly, previous studies have reported that methylation at specific CpG sites around the promoter of NR2B gene will downregulate NR2B transcription 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation